Analisis Iklan Media Sosial dan Kualitas Produk terhadap Keputusan Pembelian dengan Kepuasan Pelanggan sebagai Variabel Intervening pada UMKM Sambal K’diyah Kabupaten Brebes - Novanka Yanusa; Andi Yulianto; Syariefful Ikhwan; Akbar NP Darma Wahana; Roby Setiadi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study analyzes the influence of social media advertising and product quality on purchase decisions, with customer satisfaction as a mediating variable at UMKM Sambal K’diyah in Brebes Regency. A quantitative method with SEM-PLS analysis was employed using a sample of 155 respondents. The results show that social media advertising and product quality have a significant positive effect on customer satisfaction (β = 0.630 and β = 0.373). Product quality also significantly influences purchase decisions (β = 0.664), as does customer satisfaction (β = 0.204). Furthermore, customer satisfaction mediates the relationship between both independent variables and purchase decisions. The R² values of 0.570 for customer satisfaction and 0.705 for purchase decisions indicate a strong predictive model. This study highlights the importance of digital promotion and product quality in increasing customer satisfaction and purchase decision-making.